Meningkatkan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti Menggunakan Model Problem Based Learning Berbantuan Bamboozle Kelas X Fase E SMA Budi Murni 3 Medan - Junianti Fransiska Sinabang; Y Lsukestiyarno; Marina Murliani (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Failure in Catholic religious teaching can occur because religious educators are insufficiently prepared. Apart from that, educators feel that they can teach well, so that many educators like to teach by taking shortcuts, do not prepare learning plans, are unable to implement learning methods or models to the situation and needs of students, so that the learning that takes place is monotonous and boring and students who nowadays are more preoccupied with communication media so that many of them end up busy with their own affairs, the aim of this research is to determine the increase in learning outcomes with the Bamboozle-assisted PBL method and the increase in learning achievement targets for class X students at Budi Murni Catholic High School 3 Medan, this research uses Classroom Action Research (PTK) with the Problem Based Learning (PBL) model assisted by Bamboozle. In this research, two cycles have been carried out. Overall, the application of the Problem Based Learning model assisted by Bamboozle can improve student learning outcomes. This is proven by the increase in grades. the results of P3 qualitative observations in Cycle I were 73.32 and in Cycle II namely 82.04 and the increase in post test student learning outcomes was seen from the details of the achievements of each cycle, namely in Cycle I New Developing 6 people = 24%, Eligible = 7 people = 28%, Eligible = 8 people = 32%, Proficient = 4 people = 16%. Meanwhile, in Cycle II Newly Developing = 1 person = 4%, Decent = 2 people = 8%, Capable = 5 people = 20%, proficient = 17 people = 68%, and the average score shows an increase from 76.2 in the appropriate category to 86 .8 in the advanced category.